SISTEM PENGENDALIAN PERSEDIAAN BAHAN BAKU DALAM UPAYA EFISIENSI BIAYA PERSEDIAAN PADA GALERI MUG ADVERTISING SAMARINDA - Sisca Indriani Putri (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
The inventory of raw materials in the werehouse serves as a safety stock in case customer demand increases. This research aims to determine the economic order quantity of raw materials and calculate the efficiency of the company’s inventory costs during 2021-2022. This study is descriptive research with a quantitative approach using primary and secondary data sources. Data collection techniques included observation, interviews, and lilerature studies. The research result show that applying the EOQ (Economic Order Quantity) method can optimize the company’s inventory-related costs. The economic order quantity for 2021 was 4,000 pieces of mugs, and for 2022, it was 6,600 pieces. The inventory cost efficiency obtained using the EOQ method was IDR 1,638,688.73 in 2021 and IDR 3,059,465.05 in 2022. Recommendations are given to the company to conduct evaluations and apply the EOQ method to addres inefficiencies in inventory cost expenditures.